Sensitivity Analysis for Nonlinear Set-Valued Variational Equations in Banach Framework - A. Farajzadeh; Salahuddin (Journal of Function Spaces and Applications)
The main purpose of this paper is to study the sensitivity analysis for nonlinear set-valued variational equations based on -resolvent operator technique. The obtained results encompass a broad model of results.